A Restorative Justice Approach to The Settlement of The Persecution Crime At Police Central Barumun - Chandra Aulia Putra; Madiasa Ablisar; Mahmud Mulyadi; Marlina (Mahadi: Indonesia Journal of Law, 2023)
It is hoped that the crime of persecution, both severe and light persecution, can be resolved by using approaches that are capable of resolving the criminal act of persecution in the jurisdiction of the Barumun Tengah Police. For example, 3 (three) cases of persecution have been successfully resolved using a restorative justice approach. Currently, the settlement of criminal acts of persecution has prioritized the principle of restorative justice by mediating and paying compensation and medical expenses to victims. The problems in this study, namely: the legal regulation of a restorative justice approach in resolving criminal acts of persecution; the process of settlement with restorative justice against criminal acts of persecution at the Barumun Tengah Police; obstacles and efforts of investigators in resolving criminal acts of persecution through restorative justice at the Barumun Tengah Police. This research is a study of the legal theory of justice which is carried out by applying a scientific analytical process. The data used is secondary data which is supported by empirical data. The data used in legal research is sourced from primary, secondary, and tertiary legal materials. Secondary data collection was carried out using library research techniques and data collection tools in the form of document studies. Empirical data were collected using field study techniques and data were collected through in-depth interviews. Data analysis used qualitative methods. Conclusions are drawn using the inductive method. The results of the study show that: The legal arrangement of a restorative justice approach in resolving criminal acts of persecution to date, starting from the level of investigation, prosecution, to trial; The process of resolving with restorative justice against criminal acts of persecution at the Barumun Tengah Police, starting from the pre-restorative justice stage, restorative justice stage, and post-restorative justice stage; The most conspicuous obstacle is the legal culture barrier related to requests for compensation by the victim's family which the perpetrators cannot fulfill.